World health organization-package of essential noncommunicable disease intervention in iranfs health system based on 5As healthy lifestyle counseling model: A randomized-controlled trial protocol - Najmolmolook Amini; Sakineh Rakhshanderou; Ali Ramezankhani; Mohtasham Ghaffari (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: The Iran Package for Essential Noncommunicable Disease (Ira-PEN) program has been established since 2018 with the aim of controlling and caring of noncommunicable diseases (NCDs) as well as their underlying causes in Iran. In this study protocol, a healthy lifestyle module will be used for the first time in Iran, which was recommended in 2018 by the World Health Organization to train health workers. This module relies on the 5As model, a training intervention design, then, implement, evaluate, and present the results to the managers and decision makers of the Ira-PEN program. MATERIALS AND METHODS: This study will be performed in 2 stages, including 2 steps per stage. The first stage involves designing the 2 steps and validation of the healthy lifestyle counseling skills tool. The tool will encompass a health counseling evaluation checklist and a counseling assessment questionnaire according to the counseling recipients. The second stage also entails 2 steps; designing a training program for health workers in the field of healthy lifestyle counseling based on the Oles-Cement model followed by implementation and evaluation. CONCLUSIONS: The training program and the results obtained in this study will be presented to the managers and decision makers of both the Ira-PEN program and NCDs control in Iran, and it is suggested to enhance the training program, network, and educational curriculum of health workers in providing healthy lifestyle counseling to play a more effective role in changing the public behavior toward a healthy lifestyle and preventing the risk factors of NCDs.